Inovasi Perpustakaan Desa dalam Menggerakkan Literasi Dengan Pendekatan dan Pemberdayaan Masyarakat Desa Pangkur - Risma Eanggar Rahayu; Prasasti Mubina Sari; Allinsya Dinar Ahmad (Universitas PGRI Madiun, 2026)
The low literacy rate in rural areas is often triggered by limited access to reading materials and minimal community involvement in managing supporting facilities. This study aims to analyze the innovations implemented by Pangkur Village Library in driving literacy through a participatory approach and empowering the local community. This study uses a qualitative method with a case study approach. Data were collected through participatory observation, in-depth interviews with library managers, village officials, and community leaders, as well as document analysis related to the library's work programs. The results show that Pangkur Village Library has successfully carried out transformation through three main innovations: (1) diversification of services based on social inclusion, (2) the use of digital technology to expand access to information, and (3) active collaboration with local communities (such as Karang Taruna and PKK) in organizing educational activities. Community empowerment is carried out by involving residents not just as book consumers, but also as the driving force behind literacy activities and mentors for practical skills.